2005
DOI: 10.2184/lsj.33.262
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of an ArF Excimer Laser for Microlithography by Means of Gaseous Impurity Control

Abstract: The effect of small amounts of gaseous additives and impurities on ArF laser performance has been studied. It has been found that the output characteristics of the ArF laser improves significantly at a xenon concentration of 10 ppm but strongly deteriorates at impurity concentrations above 10 ppm of e.g. O2, CF4 and HF, especially, at high laser repetition rates. A new laser discharge chamber has therefore been developed using metal seals and coating the inner chamber walls with thin fluoride layers. The layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The latter requires a custom-made laser chamber that suppresses the generation of impurity gases. [11][12][13] However, even for a high-purity gas containing Xe at 10 ppm inside the custom-made laser chamber, we observed a steplike decrease in the output energy of the ArF excimer laser under burst-mode operation. The steplike energy decrease occurred just after the first circulation of the laser gas in the chamber.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…The latter requires a custom-made laser chamber that suppresses the generation of impurity gases. [11][12][13] However, even for a high-purity gas containing Xe at 10 ppm inside the custom-made laser chamber, we observed a steplike decrease in the output energy of the ArF excimer laser under burst-mode operation. The steplike energy decrease occurred just after the first circulation of the laser gas in the chamber.…”
Section: Introductionmentioning
confidence: 70%
“…Various tests [12][13][14] concerning the steplike energy decrease of the ArF excimer laser confirmed that the energy recovers after a rest time of approximately 0.2 s during burst operation, and that the ratio of the decrease in the energy decreases with increasing gas temperature. Because the absorbing compound F x O y is unstable, its dissociation time and the dependences of its concentration on gas temperature and initial oxygen concentration were investigated.…”
Section: Temporal Variations In Absorption At 193 Nm For Different Ga...mentioning
confidence: 91%
See 2 more Smart Citations
“…It is well known that both parameters are significantly improved by adding a small amount (typically 10 ppm) of xenon (Xe) 9,10) and by controlling concentration of impurity gases such as oxygen (O 2 ) and hydrogen fluoride (HF) to be below 10 ppm. 11,12) In order to maintain the concentration of impurities at the lowest level, we have developed a specially designed laser chamber 13) that can suppress the generation of impurity gases. However, even for a high-purity gas containing Xe at 10 ppm and the special laser chamber, we observed a steplike decrease of the output energies of the ArF excimer laser under the burst operation.…”
mentioning
confidence: 99%